Alberto José de Sampaio (1881-1946): contexto, vida e obra de um conservacionista brasileiro - Oliveira, Arthur Henrique de (2009)
In Brazil, the critical conscience in relation to environmental degradation generally is identified as something recent, a problematic imported exogenous from countries developed by the influence of the international environmentalist movement whose expansion occurred during the sixties. However, some thinkers and researchers of different areas of the knowledge of the beginning of century XX seem to have helped with important contributions for genesis of the environmental thought and critical in the country a long time before than conventionally is thought as being the moment of origin of this type of discussion. The discussions that occurred about the environmental questions in the first decades of century XX would culminate, late in the thirties, in the establishment of the first legal mechanisms of protection to the nature and in the Primeira Conferência Brasileira de Proteção a Natureza. Organized by the Society of the Friends of the Trees, it counted on strong support and infrastructure of the Museu Nacional do Rio de Janeiro, being Alberto Jose de Sampaio, botanical and teacher of this institution, its reporter. By the relevance of the activities of Alberto Sampaio we made as central object of our studies his book Biogeographia Dynamica: a natureza e o homem no Brasil (1935). This dissertation begins with the presentation of our author, the historical, social, economic and political context in the thirties, and his participation in institutions as the Brazilian Academy of Sciences and civil organizations that dedicated its work to the conservationist cause. We also pointed out the importance of the research institutes and some personalities whose names had been linked up with the protection to nature, beyond treating to the first areas protected in Brazil and the main institutional instruments to protection to nature, and the Alberto Sampaio s ideals conservationists and for last, we present our final consideration, detaching that the concerns about the conservation and the preservation of the natural elements, in Brazil, is not so recent, as one suppose mistakenly